Cross-Protective Immunity against O`Nyong-nyong Virus Afforded by a Novel Recombinant Chikungunya Vaccine - Partidos, Charalambos D. (2012)
Emerging mosquito-borne alphavirus infections caused by chikungunya virus (CHIKV) oro`nyong-nyong virus (ONNV) are responsible for sporadic and sometimes explosive urban outbreaks. Currently, there is no licensed vaccine against either virus. We have developed a highly attenuated recombinant CHIKV candidate vaccine (CHIKV/IRES) that in preclinical studies was demonstrated to be safe, immunogenic and efficacious. In this study we investigated the potential of this vaccine to induce cross-protective immunity against the antigenically related ONNV. Our studies demonstrated that a single dose of CHIKV/IRES elicited a strong cross-neutralizing antibody response and conferred protection against ONNV challenge in the A129 mouse model. Moreover, CHIKV/IRES immune A129 dams transferred antibodies to their offspring that were protective, and passively transferred anti-CHIKV/IRES immune serum protected AG129 mice, independently of a functional IFN response. These findings highlight the potential of the CHIKV/IRES vaccine to protect humans against not only CHIKV but also against ONNV- induced disease.